Denmark : Detailed Assessment of Anti-Money Laundering and Combating the Financing of Terrorism. (IMF Staff Country Reports; Country Report ;, 2007)
This paper discusses key findings of the Detailed Assessment of Anti-Money Laundering and Combating the Financing of Terrorism (AML/CFT) for Denmark. It describes and analyzes AML/CFT measures in place in Denmark, and provides recommendations on how certain aspects of the system could be strengthened. It also sets out Denmark's levels of compliance with the Financial Action Task Force Forty (FATF) 40+9 Recommendations. The assessment reveals that Denmark has a solid AML/CFT framework, recently updated with a new AML/CFT law that should provide a sound basis for an effective AML/CFT regime.